Thermally modulated shape memory alloy friction pendulum (tmSMA‐FP) for substantial near‐fault earthquake structure protection. Issue 11 (12th April 2017) - Gur, Sourav; Frantziskonis, George N.; Mishra, Sudib K.
Summary: Vibration control of structures under near‐fault earthquakes by employing a friction pendulum supplemented with thermally modulated shape memory alloy (SMA) springs as damper system is studied. Temperature modulation of the SMA spring during the earthquake effectively alters its hysteretic energy dissipation capacity and thereby the control efficiency of the isolation system. The response of a structure with the isolation system is evaluated through nonlinear dynamic time‐history analysis under a set of recorded near‐fault ground motions. Through temperature modulation that effectively yields a large SMA hysteretic energy dissipation, the hybrid friction pendulum system with SMA temperature modulation shows enormous control efficiency. A parametric study reveals that under a wide range of conditions, the thermally modulated SMA friction pendulum isolation system shows improved control efficiency over conventional friction pendulum and SMA friction pendulum isolation systems. Further, the temperature‐tuned SMA hysteresis loops substantially suppress the high frequency components of earthquake motions, thus reducing the possibility of damage to the structure.